ACQUISITION OF SONATA FINANCE NBFC BY KOTAK MAHINDRA: A STRATEGIC FINANCIAL INTEGRATION - Alka Chaudhary, Palak Nangia (Journal of Informatics Education and Research, 2025)
Mergers and acquisitions are crucial in influencing the financial environment, allowing companies to broaden their market reach and improve operational effectiveness. This study examines the strategic financial integration of Sonata Finance NBFC with Kotak Mahindra Bank, evaluating its impact on the bank’s growth, financial stability, and market competitiveness. This study analyses the expected synergies, critical financial performance elements, and possible challenges in the integration process by comparing Kotak Mahindra Bank’s acquisition of Sonata Finance NBFC with its merger with ING Vyasa Bank in 2014. It adopts an analytical perspective, focusing on financial indicators, regulatory aspects, and anticipated consequences after the merger. The report examines the acquisition's impact on financial inclusion in India and its role in Kotak Mahindra's long-term growth strategy within the microfinance sector. By examining this acquisition through both strategic and financial lenses, the study enhances comprehension of M&A-fueled expansion in the banking and NBFC industries. The research offers perspectives on the financial and operational factors associated with substantial acquisitions, presenting a structure for assessing their enduring effects on financial entities.